1948
DOI: 10.1017/s0022029900005185
|View full text |Cite
|
Sign up to set email alerts
|

372. Control of the moisture content and ‘body-firmness’ of cheddar cheese

Abstract: Cheesemaking experiments were carried out to investigate the moisture-retaining characteristics of curd made from milks of varying fat and casein content. The results indicate:(a) That milk fat helps to retain moisture in a cheese curd. The higher the proportion of fat present the more drastic the treatment required in the cheese vat to reduce the moisture content of the finished cheese to the desired level. A higher cooking temperature, more dry-stirring of the curd and a larger proportion of salt are all nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
3
0
3

Year Published

1993
1993
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 6 publications
4
3
0
3
Order By: Relevance
“…This is consistent with Whitehead (1948), who found J curd to have improved syneresis compared with H-F. Following the same cheesemaking process, J curd retained 25% more whey.…”
Section: Cheesemaking Processsupporting
confidence: 88%
See 4 more Smart Citations
“…This is consistent with Whitehead (1948), who found J curd to have improved syneresis compared with H-F. Following the same cheesemaking process, J curd retained 25% more whey.…”
Section: Cheesemaking Processsupporting
confidence: 88%
“…This lack of difference in sensory properties is supported by Whitehead (1948), except that the latter study found firmness to be greater in J cheese, which was not the case in our study. The lack of effect of J milk on texture is surprising because the increase in fat in DM (Table 3) should have decreased cheese firmness (Martin et al, 2000).…”
Section: Cheese Sensory Propertiessupporting
confidence: 75%
See 3 more Smart Citations